1992
DOI: 10.1007/bf01744560
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu arteritis: Follow-up studies for 20 years

Abstract: We reviewed retrospectively 126 (5 male, 121 female) patients suffering from Takayasu arteritis who had been treated in our clinics from 1971 to 1990. The patients' ages ranged from 19 to 80 yrs old (1990) with a mean age of 48.7 +/- 11.8 years. HLA typing analysis in 98 patients revealed that 45 patients (47%) were confirmed as carrying the Bw52 antigen, a high result that is statistically significant as compared with that in healthy Japanese. Arteriograms (performed in 75 patients) revealed that 28 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…The distribution of HLA alleles among different populations is variable, and therefore, the results are also different. For example, HLA-B52 is associated with susceptibility to TA in the Japanese, and B52-positive patients need to be treated with a higher dose of steroids for a longer period as compared with B52-negative patients [25]. Furthermore, HLA A‫,1003ء‬ HLA B‫,1025ء‬ and DRB1‫2051ء‬ alleles increase the susceptibility to TA, whereas A‫2062ء‬ might protect against TA in Koreans [12].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of HLA alleles among different populations is variable, and therefore, the results are also different. For example, HLA-B52 is associated with susceptibility to TA in the Japanese, and B52-positive patients need to be treated with a higher dose of steroids for a longer period as compared with B52-negative patients [25]. Furthermore, HLA A‫,1003ء‬ HLA B‫,1025ء‬ and DRB1‫2051ء‬ alleles increase the susceptibility to TA, whereas A‫2062ء‬ might protect against TA in Koreans [12].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the prevalence of the HLA-B52 allele, and the effect of its presence on the clinical characteristics of TA. 8, 9 This study was approved by the Ethics Review Board at Tokyo Medical and Dental University.…”
Section: Methodsmentioning
confidence: 99%
“…Many cases in the HLA-B52-allele-positive group followed the typical clinical course of TA. In prior studies, associations of HLA-B52 allele with more extensive aortic disease and refractoriness to corticosteroids were also observed (Numano et al 1982;Moriwaki and Numano 1992;Kitamura et al 1998), which might suggest an association of HLA-B52 allele with more active and severe disease.…”
Section: Discussionmentioning
confidence: 84%
“…Over 20 years ago it was reported that features of a more severe and refractory disease are also associated with the presence of HLA-B52 in Japan: higher blood pressure, acute phase response, and a need for corticosteroids (Numano et al 1982;Moriwaki and Numano 1992). However, Takamura et al (2012) subsequently reported that no significant differences were observed between HLA-B52-positive patients and HLA-B52-negative patients in the following clinical characteristics: age at disease onset, distribution of arteritis, pulmonary involvement, aortic regurgitation (AR), systemic hypertension, steroid resistance, and recurrence rate.…”
Section: Introductionmentioning
confidence: 99%